Mental Effort When Playing, Listening, and Imagining Music in One Pianist’s Eyes and Brain - Endestad, Tor; Godøy, Rolf Inge; Sneve, Markus Handal; Hagen, Thomas; Bochynska, Agata; Laeng, Bruno (Frontiers in Human Neuroscience, 2020)
We investigated volitional imagery and ‘musical effort’ with a professional pianist and non-professional pianists and non-musicians by use of pupillometry and fMRI. We confirmed that musical imagery has strong commonality with music listening in both experts and naïve individuals. The combined approach of psychophysiology and neuroimaging revealed the cognitive work during musical activities like playing, listening, and simply imagining the music. Our objective measure of effort, via pupil size, showed that pupil diameters were largest when ‘playing’ (regardless whether there was sound produced or not) compared to conditions with no movement (i.e., ‘listening’ and ‘imagery’). We found positive correlations between pupil diameters of the professional pianist during different conditions with the same piano piece (i.e., normal playing, silenced playing, listen, imagining), which might indicate similar degrees of load on cognitive resources as well as an intimate link between the motor imagery of sound-producing body motions and gestures. Neuroimaging with fMRI provided evidence for a relationship between noradrenergic activity and mental workload or attentional intensity within the domain of music cognition. We found effort related activity in the superior part of the locus coeruleus and, similarly to the pupil, the listening and imagery engaged less the LC-NE system than the motor condition. Pianists attended more intensively to the most difficult piece than non-musicians, since they showed larger pupils than non-musicians only for the most difficult piece. Non-musicians seemed to be the most engaged group by listening, suggesting that the amount of attention allocated for a same task may follow a hierarchy of expertise demanding less attentional effort in expert or performers than in novices. We found only weak evidence for a commonality between subjective effort ratings and the objective effort gauged with pupil diameter during listening. We suggest that psychophysiological methods like pupillometry could index mental effort in a manner that is not ‘observable’ in awareness or via introspection